TEACH Kitchen: a Chronological Review of Accomplishments - Jung Chae; Benjamin Ansa; Selina Smith (Georgia Southern University, 2017)
Background: The Eating and Cooking Healthy (TEACH) Kitchen was founded at the Medical College of Georgia in 2015 as a nutrition-based intervention to combat the high prevalence of obesity and obesity-related chronic diseases in the area of Augusta, Georgia. Despite the importance of diet in the management of chronic diseases, inadequate nutrition education among patients and healthcare providers presents a barrier. The purpose of TEACH Kitchen is to address this gap. Methods: TEACH Kitchen is as a student-led initiative that promotes healthy cooking among medical students and patients with chronic diseases. Healthy nutrition and cooking classes are held during the academic year. Participants spend four weeks on each of four modules: obesity, hypertension, hyperlipidemia, and diabetes mellitus. Data collection, which began in January 2017, is currently on going. TEACH Kitchen has collaborated with Augusta University, Sodexo, and Kohl's. Results: Currently, TEACH Kitchen has enrolled 14 patients and 6 children. Anticipated results include measurements of preand post-intervention changes in knowledge, attitudes, beliefs, and competence in nutrition, as well as differences in clinical indicators, including body mass index, blood pressure, lipid profile, and HbA1c. Conclusions: TEACH Kitchen is the first medical school-based nutrition/cooking education initiative in Augusta, Georgia. It provides patients and medical students with hands-on healthy nutrition/cooking experience with the goal of decreasing the prevalence and improving the outcome of obesity-related diseases.